Sustentabilidade dos agroecossistemas com barragens subterrâneas no semiárido paraibano - Ferreira, Gizelia Barbosa (2011)
The influence of subsurface dams in semi-arid agro-ecosystem sustainability must be studied from a systemic perspective to evaluate the dynamic sociopolitical, cultural, economic and environmental involving farmers as actors in the research. The farmers also perform the non-agricultural activities seeking to generate more income for the family, and thus enable social reproduction, economic and environmental, not taking away its rural identity. We used qualitative methods based on participation facilitated by the tools of methods Participatory Rural Appraisal - PRA and the Evaluating the sustainability of Integrated Peasantry Systems MESMIS Framework, in order to assess the sustainability of two properties with subsurface dams in semiarid region of Paraíba State, Brazil. It was found from the perception of families, the 01 Property, Family Santos, got a reasonable level of sustainability (3.1), from the average 3.4, 2.8, and 3.0 obtained for the dimensions environmental, social and economic, respectively. While 02 Property, Family Lira reached a good level, with overall mean 4.1, obtained through the medium, 4.1, 4.2 and 4.3, for environmental, social and economic, respectively. Quantitative indicators for the assessment of physical, chemical and biological soil proved to be efficient in comparison with subsurface dam environments (BS) under the conventional system and native, were observed higher levels of OM accumulation in the area of the BS and increased microbial activity in the native forest. The families participating in the study, although they are soon in the process of agroecological transition, progress toward a more sustainable agroecosystem, and the subsurface dam as a potential technology to improve and balance the ecological processes of the production system of family farming semiarid.